PENINGKATAN PERILAKU PROSOSIAL ANAK MELALUI METODE BERMAIN PERAN MAKRO PADA USIA 4-5 TAHUN DI TAMAN KANAK-KANAK IMMANUEL PONTIANAK. - Levina Faustine Cristanti; Marmawi R Marmawi R; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to determine the increase in prosocial behavior of children through the method of playing macro roles in children aged 4-5 years at the Immanuel Kindergarten in Pontianak. The research method used was classroom action research conducted in 2 cycles. Each cycle is done in 2 meetings. The data source of this study were children aged 4-5 years of the A4 group of 25 children and the data were observation sheets for teachers, children and documentation. Data processing uses a percentage calculation method. The conclusion of the results of the method of playing macro roles for children aged 4-5 years at the Immanuel Pontianak Kindergarten in Increasing the prosocial behavior of children increased in cycle 2 meeting 2 on the aspect of children being enthusiastic in playing games with friends reaching 96% with very good categories, children obey the rules (patiently waiting their turn) reaches 100% with very good categories, children respect others (working together) reaches 100% with very good categories and children show concern (helping) reaching 92% with very good categoriesKeywords: Children Aged 4-5 Years, Child Prosocial Behavior, Macro Role Playing Method